Literature Review: Evidence of Day-of-the-Week Effect in Cryptocurrency Market - Kie, Tan Sze; Jiun, Ricky Chia Chee (STIE Malangkucecwara, 2024)
This study provides a comprehensive analysis of the anomaly of day-of-the-week effect found in cryptocurrency market. Its primary objective is to synthesize existing literature and offer an overview of the current understanding of this phenomenon, while identifying trends and research gaps. A systematic literature review was conducted across three major databases—Emerald Insight, Science Direct, and JSTOR—using the keywords